Measuring Vasculitis with Numbers: Outcome Scores - Batu, Ezgi D.; Ozen, Seza (Current Rheumatology Reviews, 2020)
Primary Systemic Vasculitides (PSV) are a heterogeneous group of diseases. Outcome scores are important to evaluate vasculitis patients in a more structured and standard way and these help physicians to predict patients with poor prognosis or high risk of relapse. Furthermore, we need reliable outcome measures for clinical trials. There are a number of vasculitis outcome scores available in the clinical practice with different strengths and limitations. These are mainly measures of disease activity, disease damage, response to treatment and quality of life. Birmingham Vasculitis Activity Score (BVAS) and its pediatric version aim to evaluate a wide scope of PSV. On the other hand, some outcome studies have focused on a single vasculitis type since the whole group includes different diseases with heterogeneous clinical features. The aim of this review is to provide an overview on outcome measures currently being used in the evaluation of patients with PSV. We mainly focus on immunoglobulin A vasculitis/Henochschönlein purpura, Kawasaki disease, anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis, polyarteritis nodosa, Takayasu arteritis and Behçet’s disease.
Keywords: FFS